Culture Minister to Open Laventille Pan Workshop. - Unknown (Newsday)
Culture Minister Ganga Singh is set to open a pan management workshop that forms part of the Laventille Steelband Festival. Speakers at the workshop will include Professor Lloyd Best, pan's first-lady Pat Bishop, former Finance Minister Brian Kuei Tung and television producer, Tony Hall.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Musicians -- Training of -- Trinidad and Tobago; Steel drum (Musical instrument) -- Education -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Music -- Instruction and study